Prognostic value of tumor-infiltrating FoxP3+ regulatory T cells in cancers: a systematic review and meta-analysis - Shang, Bin; Liu, Yao; Jiang, Shu-juan; Liu, Yi (Scientific reports, 2015)
The prognostic value of FoxP3 + regulatory T cells (Tregs) in cancer remains controversial. We did a meta-analysis to assess the prognostic effect of FoxP3 + Treg across different types of cancer and to investigate factors associated with variations in this effect. PubMed, Embase, Cochrane CENTRAL and Scopus were searched to identify eligible studies. In total, we analyzed 76 articles encompassing 17 types of cancer and including 15,512 cancer cases. The overall pooled analysis including all types of cancer suggested FoxP3 + Tregs had a significant negative effect on overall survival (OS) (OR 1.46, P < 0.001), but the prognostic effect varied greatly according to tumor site. High FoxP3 + Tregs infiltration was significantly associated with shorter OS in the majority of solid tumors studied, including cervical, renal, melanomas and breast cancers, et al ; whereas, FoxP3 + Tregs were associated with improved survival in colorectal, head and neck and oesophageal cancers. The stratified analysis suggested the molecular subtype and tumor stage significantly influenced the prognostic value of FoxP3 + Tregs in certain types of cancer. In conclusion, our meta-analysis suggests that the prognostic role of FoxP3 + Tregs was highly influenced by tumor site and was also correlated with the molecular subtype and tumor stage.